History of Islamic Civilization during the Prophethood (610-633 AD) - Muhlis, Wachida; Hizbullah, Hizbullah; Nirmayanthi, Andi; Said, Said Al Zaiim Bani; Alfarryzy, Muhammad (Universitas Islam Negeri Sumatera Utara, 2025)
The history of Islamic Civilization during the Prophethood (610-633 AD) is very important to study. This paper aims to understand three things: first, the concrete form of the development of Islam; Second, the factors that influence the development of Islam; The three implications that affect the development of Islam. The method used is library research. Literature study using articles as the primary data source and journals that have been selected according to the relevance of the title. The most important findings in research on the history of Islamic civilization during the Prophetic Period include three; First, the Prophet Muhammad received a prophetic treatise and then started preaching Islamic teachings amidst the misguidance of the Meccan Jahiliyah community. Second, the Islamic ummah is led by the best role model of all time, namely the Prophet Muhammad. In his leadership, Muhammad laid the foundation of social life (ukhuwah Islamiyah) of brotherhood among Muslims, bringing brotherhood between the Muhajirin who moved from Mecca to Medina and the residents of Medina ansar who embraced Islam and helped the Muhajirin. Third, the formation of Islamic civilization in 622 AD when the Prophet migrated from Mecca to Medina, and there was a major change in human history starting from Medina as the center of civilization. Studying the Islamic development of the Prophetic Period can broaden the body of knowledge, especially in the field of Islamic history and culture.